2019
DOI: 10.1002/hipo.23153
|View full text |Cite
|
Sign up to set email alerts
|

The polarity and properties of radial glia‐like neural stem cells are altered by seizures with status epilepticus: Study using an improved mouse pilocarpine model of epilepsy

Abstract: In the adult mouse hippocampus, new neurons are produced by radial glia‐like (RGL) neural stem cells in the subgranular zone, which extend their apical processes toward the molecular layer, and express the astrocyte marker glial fibrillary acidic protein, but not the astrocyte marker S100β. In rodent models of epilepsy, adult hippocampal neurogenesis was reported to be increased after acute and mild seizures, but to be decreased by chronic and severe epilepsy. In the present study, we investigated how the seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 70 publications
(135 reference statements)
3
10
0
Order By: Relevance
“…4A-C). Comparison of sham operates of naïve and epileptic mice showed that Type 1 progenitors were significantly reduced in mice with SE, consistent with prior studies (Singh et al, 2015; Sasaki-Takahashi et al, 2020); GABA progenitor transplantation did not rescue Type 1 progenitors (Fig. 4D).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…4A-C). Comparison of sham operates of naïve and epileptic mice showed that Type 1 progenitors were significantly reduced in mice with SE, consistent with prior studies (Singh et al, 2015; Sasaki-Takahashi et al, 2020); GABA progenitor transplantation did not rescue Type 1 progenitors (Fig. 4D).…”
Section: Resultssupporting
confidence: 90%
“…While additional studies are necessary to determine the precise molecular and cellular mechanisms for increasing survival and normalizing the direction of migration of adult-born GCs in TLE mice with GABAergic transplants, our findings suggest that the exogenous GABAergic cells may provide the signals for these phenomena. In agreement with prior studies, we found that mice with pilocarpine-induced epilepsy had reduced numbers of normal Type 1 progenitors with radial processes into the GCL (Sierra et al, 2015;Singh et al, 2015;Sasaki-Takahashi et al, 2020) but increased inverted Type 1 progenitors.…”
Section: Enhanced Radial Migration Of Adult-born Granule Cells Into T...supporting
confidence: 93%
See 3 more Smart Citations